2015
DOI: 10.1038/nrneph.2015.193
|View full text |Cite
|
Sign up to set email alerts
|

HIF prolyl hydroxylase inhibitors for the treatment of renal anaemia and beyond

Abstract: Small-molecule stabilizers of hypoxia inducible factor (HIF) are being developed for the treatment of renal anaemia. These molecules inhibit prolyl hydroxylase domain-containing (PHD) enzymes, resulting in HIF activation and increased production of erythropoietin. Currently, renal anaemia is treated with recombinant human erythropoietin or related analogues, referred to as conventional erythropoiesis stimulating agents (ESAs). Advantages of PHD enzyme inhibitors over conventional ESAs include their oral admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
219
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(221 citation statements)
references
References 147 publications
(147 reference statements)
0
219
1
1
Order By: Relevance
“…HIF stabilization via PHD inhibition promotes erythropoiesis by stimulating endogenous EPO secretion and improving iron availability [20]. Prior studies of vadadustat in healthy volunteers and CKD patients demonstrated modest increases in endogenous EPO levels - which were similar to those observed following exposure to moderate altitude [21] - as well as preserved physiologic diurnal variation of serum EPO levels [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…HIF stabilization via PHD inhibition promotes erythropoiesis by stimulating endogenous EPO secretion and improving iron availability [20]. Prior studies of vadadustat in healthy volunteers and CKD patients demonstrated modest increases in endogenous EPO levels - which were similar to those observed following exposure to moderate altitude [21] - as well as preserved physiologic diurnal variation of serum EPO levels [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The modulation of the activity of these enzymes could be beneficial for the treatment of a variety of diseases, therefore, a large number of PHD2 inhibitors have been developed and are now in late stage clinical trials for the treatment of anemia and chronic kidney diseases [8][9][10][11][12][13]. Several companies have reported PHD inhibitors in clinical development for the treatment of ischemia and anemia associated with chronic renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Advantages of this new class of drug include oral administration, low immunogenicity, product stability and possibly lower costs as well as potential cardiovascular benefits (84).…”
Section: Hif-ph Inhibitorsmentioning
confidence: 99%